Active plasmonics and tuneable plasmonic metamaterials - Zayats, A. V. (Anatoly V.); Maier, Stefan A.; Wiley eBooks (Hoboken, N.J. : Wiley : Science Wise, 2013)
"This book, edited by two of the most respected researchers in plasmonics, gives an overview of the current state in plasmonics and plasmonic-based metamaterials, with an emphasis on active functionalities and an eye to future developments. This book is multifunctional, useful for newcomers and scientists interested in applications of plasmonics and metamaterials as well as for established researchers in this multidisciplinary area"--
"Presents contributions from world's leading authorities in plasmonics, covering active plasmonics from basic principles to the most recent breakthroughs"--
9.2 WIRE MEDIUM LENS AT THE MICROWAVE FREQUENCIES9.3 MAGNIFYING AND DEMAGNIFYING LENSES WITH SUPER-RESOLUTION; 9.4 IMAGING AT THE TERAHERTZ AND INFRARED FREQUENCIES; 9.5 NANOLENSES FORMED BY NANOROD ARRAYS FOR THE VISIBLE FREQUENCY RANGE; 9.6 SUPERLENSES AND HYPERLENSES FORMED BY MULTILAYERED METAL-DIELECTRIC NANOSTRUCTURES; REFERENCES; Chapter 10: Active and Tuneable Metallic Nanoslit Lenses; 10.1 INTRODUCTION; 10.2 POLARIZATION-SELECTIVE GOLD NANOSLIT LENSES; 10.3 METALLIC NANOSLIT LENSES WITH FOCAL-INTENSITY TUNEABILITY AND FOCAL LENGTH SHIFTING.
Includes bibliographical references.
John Wiley and Sons
Keywords: Plasmons (Physics); Metamaterials; Photonics; Surface plasmon resonance; SCIENCE -- Molecular Physics; SCIENCE -- Energy; SCIENCE -- Mechanics -- General; SCIENCE -- Physics -- General; Metamaterials; Plasmons (Physics); Electronic books